TANGGAPAN PENGUNJUNG PADA DESTINASI WISATA TOLUK JANGKANG DI KECAMATAN TUALANG KABUPATEN SIAK PROVINSI RIAU - Sofia Deviana Utami; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine and analyze the response of tourists to Toluk Jangkang Tourism Destination. This study uses a quantitative method with a descriptive approach to describe and explain the situation that occurs by collecting data and information in the field.. In this study, the data collection techniques used were observation, questionnaires and documentation. Based on the results of the questionnaire, it shows that the response of visitors to the Toluk Jangkang Tourism Destination in Tualang Sub District of Siak Regency is quite good, where the concepts used are Destination Attractions, Destination Facilities, Accessibility, Image, and Price. The tourism response to Toluk Jangkang Tourism Destination in Tualang Sub District of Siak Regency in the sub-variable of destination attractions, destination facilities, accessibility and image are considered quite good by visitors who have visited Toluk Jangkang Tourism Destination, while for the price sub-variable it is considered good by visitors who have visited Toluk Jangkang Tourism Destination.Key words : Responses, Visitors and Tourism Destination